Numerical studies of scrape-off layer connection length in Wendelstein7-X. (16th November 2017) - Sinha, P.; Hölbe, H.; Pedersen, T.S.; Bozhenkov, S.
Abstract: The distribution of particles and power flux to plasma-facing components play a critical role in the design of next-generation fusion devices. In particular, it is a challenge to bring down the peak heat fluxes onto the divertor to manageable levels (of order 5 MW m − 2 ). A large value of connection length ( L c ) increases the role of cross-field transport and may lead to broader power deposition profile and lower peak heat fluxes. In low-shear stellarators like Wendelstein 7-X (W7-X) very long connection lengths, about one order of magnitude longer than those of equal-sized tokamaks, can be achieved. The flexibility of W7-X coil system allows variation of connection lengths significantly. This paper describes numerical studies that identify magnetic configurations in W7-X with particularly large and particularly small L c ; thus, the effects of L c on divertor operation can be effectively studied. It is found that a variation of a factor of 8 is possible, with average L c values as large as 426 m for a configuration developed here. It is also shown that L c itself, for a given magnetic configuration, varies strongly, potentially complicating an experimental analysis of its effects.